(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2005)
A relative study of various linear simultaneous equation solvers has been made. The profile solver and the block solver which have been considered to be most effective solution techniques have been implemented. Medium to large sized structural analysis problems have been analyzed. The comparison of solution time, total execution time and the incore memory requirement have been made. The suitability of solvers for various sized problems has also been discussed.